Tools of preventive police activity in the field of combating cruelty to animals - V. S. Seliukov; А. І. Potikhenskyi (Bulletin of Kharkiv National University of Internal Affairs)
Theoretical and practical approaches to the organization of the activities of police units recently, especially in the conditions of martial law, require rethinking and more efficient and effective mechanisms. Martial law significantly increased the level of trust of the population in the police, on the one hand, and on the other hand – created even more difficulties in the organization of their activities. Determining one of the priorities of the police activity of ensuring people’s rights, reformatting activities from penal to service branch, ensuring safety and order in society – all this contributes to the process of intensifying the improvement of views on the need to ensure the formation of high moral standards and a high level of legal culture in society. The specified provision on changing the theoretical orientation of scientific approaches to practical ones. It follows that prevention, as the main type of police activity, should be aimed at meeting the needs of society, and not at developing indicators of crime detection.